An Implementation of STEAM Approach: Junior High School Mathematics and Science Teachers' Perceptions and Obstacles - Isti Hidayah; Arif Widiyatmoko; Nazzun Sholikha Nurin; Agung Laksono (International Conference on Science, Education, and Technology, 2022)
STEAM approach is part of mathematics, science, and other teaching policies to facilitate students' higher-order thinking skills, including Critical Thinking, Collaboration, Communication, and Creativity. This research aims to examine both math and science teachers' perceptions and obstacles in implementing the STEAM approach, formulating teacher's preparation model in applying it. This descriptive research was conducted using survey methods by Google Form. The research subjects were 68 mathematics teachers and 42 science teachers in Semarang City. The results showed that both the perceptions of math and science teachers tend to have a positive attitude to apply the STEAM approach to science/math in the classroom with the highest average score (4.13) and the lowest average score occurs in the knowledge indicator of STEAM learning steps based on the science and math integration project (3.31). Meanwhile, the obstacle with the highest score in applying the STEAM approach for both math and science teachers is still required more knowledge about STEAM. Based on the study of perceptions and obstacles, and the existing preparation models, it is concluded that the modification of the hypothetical model can be done by strengthening the knowledge and skills of STEAM, as well as preparation practices in the Teacher Working Group/MGMP (Musyawarah Guru Mata Pelajaran) forum.